Upaya Peningkatan Kesadaran Masyarakat melalui Gotong Royong Kebersihan dan Pembuatan Plang Himbauan Untuk menjaga Kebersihan Lingkungan di Taman Kelurahan Pematang Gubernur - Situmorang, Bernando; Magfiroh, Galih; Anugra, Bima; Aldo, Muhammad; Ferdyansyah, Ferdyansyah; Nasution, Suswati; Susena, Karona Cahya; Rullyanti, Merry (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Residential areas in Pematang Gubernur Village are facing the problem of accumulated household waste, indiscriminate littering, and a lack of green open spaces, which reduce the community's sense of well-being and concern for cleanliness. This community service initiative provides a solution involving community participation through community service activities to clean the environment and the development of Pematang Park, a simple, collaboratively managed green space. The goal of this community service initiative is to raise community awareness and responsibility for maintaining environmental cleanliness and encourage sustainable public space maintenance practices. Methods used to address the problem include identifying locations with high levels of waste with residents and vi lage officials, conducting brief education sessions on clean living behaviors and household waste management, implementing mutual cooperation to clean and tidy the area, and creating a park through reforestation and simple facility arrangement. The results of this initiative show improvements in environmental cleanliness, increased community participation in community service activities, and the establishment of Pematang Park as an educational tool and a sense of ownership. These findings demonstrate that collective activities accompanied by green space management can effectively address cleanliness issues and increase community awareness.